Forest restoration to promote a fair post COVID-19 recovery in the Brazilian Amazon. (May 2022) - Celentano, Danielle; Moraes, Miguel; Ferreira, Joice; Nahur, André; Coutinho, Bruno; Rousseau, Guillaume X.; Martins, Marlucia Bonifacio; Vasconcelos, Lívia G.T. Rangel; Rodrigues, Fernanda; Freire, Rodrigo; Pinto, Andréia; Kanashiro, Milton
Abstract: Forest restoration has attracted the attention of different organizations, investors, and donors with the launch of the UN Decade for Ecosystems Restoration (2021–2030), along with climate and biodiversity commitments. Restoration can address many of mankind's challenges, such as biodiversity loss, climate change, water security, and poverty. In the Brazilian Amazon, the 28 million inhabitants are among the most vulnerable of the country, and this has only worsened during the COVID-19 pandemic. Meanwhile, millions of hectares are suitable for forest restoration. The growing demand for large-scale forest restoration projects have been prioritizing biophysical objectives (e.g., number of trees, hectares of land, and carbon) while it should be prioritizing the local people's well-being and a fair transition to a sustainable economy based on forest services' recovery. Nonetheless, many challenges need to be overcome to realize this potential. Amazonian states need to control illegality, enforce the existing policies and promote innovative ones to halt deforestation and enable large-scale restoration. Better governance and social engagement are urgently needed but depend upon, recognition of indigenous peoples and local communities' rights, needs, and knowledge. Forest restoration represents an opportunity for the emergence of a more inclusive development paradigm, much needed in the Amazon region, especially in the post COVID-19 world. Highlights: Forest restoration might be the key to an inclusive development paradigm and a fair COVID-19 recovery in the Amazon. Combining ecological and socioeconomic co-benefits is imperative for the Amazon restoration. Ignoring the social dimension of restoration may lead to the failure of restoration interventions. Strategic investments to strengthen community organization and build local capacities are paramount.